True brachial artery aneurysm: A systematic review - Alam, Syed Muhammad Hammad; Saima Moin; Rabia Gilani; Nida Jawad; Kiran Abbas; Aayat Ellahi (Journal of the Pakistan Medical Association, 2024)
Objective: To identify and critically appraise literature on true brachial artery aneurysm, exploring its demographic characteristics, aetiologies, clinical manifestations and different methods of repair along with complication rates to determine future treatment strategies. Method: The systematic review was conducted at Liaquat National Hospital, Karachi, from September 30, 2021, to November 30, 2022, in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Literature was searched on MEDLINE, EMBASE and Cochrane databases for relevant studies in English language or with English translation published till May 31, 2022. The key words used for the search were “brachial artery aneurysm”. Data was noted on a proforma and was subjected to descriptive analysis. Results: Of 113 the articles, 6 (5.3%) were retrospective studies, 7 (6.1%) were case series and 100 (88.4%) were case reports. The total number of patients involved was 157 with mean age 43.1+23.4 years (range: 2 months to 84 years). The gender was mentioned for 152(96.8%) patients; 111(73%) and 41(27%) females. The mean diameter of true brachial artery aneurysm was 36.2+17.5mm and 106(67.5%) patients presented with localised swelling, 65(41.4%) with pain, 41(26.1%) with distal ischemic symptoms, and 28(17.8%) with median nerve compression. True brachial artery aneurysms were more common in renal failure patients having a history of arteriovenous fistula creation in the affected limb and were on immunosuppressant drugs due to renal transplant 81(51.5%). Less common causes included primary/idiopathic 27(17.1%), trauma 13(8.2%), connective tissue disorders 8(5%) and vascuilits 7(4.5%). —Continue